Ending DACA Has Pragmatic and Ethical Implications for U.S. Health Care. Issue 6 (24th November 2017) - Zaidi, Danish; Kuczewski, Mark
Abstract: In 2012, Loyola University Chicago's Stritch School of Medicine became the first medical school in the United States to actively recruit and accept undocumented immigrants who received protections granted under the Deferred Action for Childhood Arrivals program that was established by presidential memorandum. By 2016, sixty‐one medical schools were considering applications from DACA recipients for admission, and more than 110 students applied. According to the Association of American Medical Colleges, sixty‐five DACA recipients matriculated in U.S. medical schools in the 2016–2017 school year. These students contribute both diversity and talent to our medical community; they could also have a significant impact on the care of underserved and immigrant populations. The recent decision by the Trump administration to rescind DACA therefore comes with serious pragmatic and ethical ramifications, impeding our medical community's efforts to develop a diverse and representative workforce committed to improving access to quality care for all patients .